Natural conception rates in subfertile couples following fertility awareness training - Frank-Herrmann, Petra; Strowitzki, Thomas (Archives of gynecology and obstetrics, 2017)
PurposeTo analyze cumulative pregnancy rates of subfertile couples after fertility awareness training.MethodsA prospective observational cohort study followed 187 subfertile women, who had received training in self-observation of the fertile phase of the menstrual cycle with the Sensiplan method, for 8 months. The women, aged 21-47 years, had attempted to become pregnant for 3.5 years on average (range 1-8 years) before study entry. Amenorrhea, known tubal occlusion and severe male factor had been excluded. An additional seven women, who had initially been recruited, became pregnant during the cycle immediately prior to Sensiplan training: this is taken to be the spontaneous pregnancy rate per cycle in the cohort in the absence of fertility awareness training.ResultsThe cumulative pregnancy rate of subfertile couples after fertility awareness training was 38% (95% CI 27-49%; 58 pregnancies) after eight observation months, which is significantly higher than the estimated basic pregnancy rate of 21.6% in untrained couples in the same cohort. For couples who had been seeking to become pregnant for 1-2 years, the pregnancy rate increased to 56% after 8 months. A female age above 35 (cumulative pregnancy rate 25%, p = 0.06), couples who had attempted to become pregnant for more than 2 years (cumulative pregnancy rate 17%, p < 0.01), all significantly reduce the chances of conceiving naturally at some point.ConclusionsTraining women to identify their fertile window in the menstrual cycle seems to be a reasonable first-line therapy in the management of subfertility.